2021
DOI: 10.3389/fpsyg.2021.736171
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Revised Collett–Lester Fear of Death Scale in a French Population

Abstract: Death and dying are processes that every human being encounters in his or her lifetime and perhaps the greatest loss an individual can suffer. In this sense, fear of death is regarded as a risk and maintaining factor of psychopathology. As such, effective and efficient measurement of this construct becomes a priority. While the Revised Collett-Lester Fear Of Death Scale (CL-FODS) is a brief, commonly used assessment, such a tool is lacking in French clinical practice. The present study aimed to adapt the revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
(71 reference statements)
0
11
0
1
Order By: Relevance
“…The results were obtained after statistically controlling for several prominent covariates. Notably, controlling for the influences of perceived disease vulnerability ( Jungmann and Witthöft, 2020 ) and fear of losing loved ones ( Mertens et al, 2020 ; Cuniah et al, 2021 ) allowed us to examine and highlight the unique effects of death anxiety on our dependent variables. Nevertheless, it is important to note that all study results remained intact when the covariates were not statistically controlled for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were obtained after statistically controlling for several prominent covariates. Notably, controlling for the influences of perceived disease vulnerability ( Jungmann and Witthöft, 2020 ) and fear of losing loved ones ( Mertens et al, 2020 ; Cuniah et al, 2021 ) allowed us to examine and highlight the unique effects of death anxiety on our dependent variables. Nevertheless, it is important to note that all study results remained intact when the covariates were not statistically controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…We measured fear of losing loved ones because (a) research has shown that fear of one’s own death should be distinguished from fear of losing significant others (see Cuniah et al, 2021 , for a recent publication) and (b) risk for loved ones has been found to be one of the strongest predictors of COVID-19-related fears ( Mertens et al, 2020 ). Thus, we used the eight-item subscale The Death of Others from The Collett-Lester’s Fear of Death Scale Version 3.0 ( Lester, 1990 ; Lester and Abdel-Khalek, 2003 ) to control for potential influences on our focal variables.…”
Section: Methodsmentioning
confidence: 99%
“…A respeito da EMMCL, destaca-se que ela foi inicialmente elaborada no final dos anos 1960 nos Estados Unidos (Collett & Lester, 1969), é um instrumento multidimensional (Venegas et al, 2011) e com a vantagem de ter validação em diversos contextos culturais (Abdel-Khalek, 2002;Tomás-Sábado et al, 2007;Quintero & Simkin, 2017;Bužgová & Janíková, 2017;Oliveira Júnior et al, 2018;Quintero & Simkin, 2020;Mondragón-Sanchez et al, 2020;Cuniah et al, 2021). A maneira como a EMMCL foi desenvolvida concebe que o medo da morte pode apresentar várias causas possíveis, ou seja, é uma variável dependente sob influência de múltiplas variáveis independentes.…”
Section: Procedimentos E Instrumentosunclassified
“…Previous studies about fear of death showed gender differences, with women scoring higher on fear of death than men [ 15 ], and the most widely accepted explanation was that women have an easier time admitting and expressing their emotions and feelings related to death [ 16 ]. However, to date, these gender differences have not been clearly explained.…”
Section: Introductionmentioning
confidence: 99%
“…The original instrument contained 36-items, however it was revised to reduce it to 28-items in 2003. Conceptually it was designed to measure fear of death in four subscales: “Your Own Death”, “Your Own Dying”, “The Death of Others” and “The Dying of Others” [ 29 ] The questionnaire has also been validated in different languages such as Czech [ 30 ], French [ 15 ] or Arabic [ 31 ]. Although the CL-FODS has been adapted to Spanish in nursing students, to the best of our knowledge, no psychometric analysis has been carried out in Occupational Therapy students [ 32 ].…”
Section: Introductionmentioning
confidence: 99%